2016
DOI: 10.1039/c6ra03397k
|View full text |Cite|
|
Sign up to set email alerts
|

Study on a hydrophobic Ti-doped hydroxyapatite coating for corrosion protection of a titanium based alloy

Abstract: In the paper, hydroxyapatite coatings enriched with Ti were prepared as a possible candidate for biomedical applications, especially for implantable devices that are in direct contact with bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Besides its use for the fabrication of medical devices (in either pure or alloyed form), Ti 4+ can be integrated as substitutional dopant in HA to enhance cells viability, proliferation and differentiation, along with the stimulation of the extra-cellular matrix mineralization [68,316]. The in vitro formation of biomimetic apatite layers on top of Ti-HA was evidenced by SBF testing irrespective of doping level (no pure HA control data were provided) [317,318]. The biological activity of Ti-HA coatings is dependent on the Ti substrate surface: a rough metallic substrate enhanced the production and mineralization of the bone matrix compared to a smoother one, therefore enhancing the osseointegration capability [316].…”
Section: Cation-substituted Hydroxyapatitesmentioning
confidence: 99%
“…Besides its use for the fabrication of medical devices (in either pure or alloyed form), Ti 4+ can be integrated as substitutional dopant in HA to enhance cells viability, proliferation and differentiation, along with the stimulation of the extra-cellular matrix mineralization [68,316]. The in vitro formation of biomimetic apatite layers on top of Ti-HA was evidenced by SBF testing irrespective of doping level (no pure HA control data were provided) [317,318]. The biological activity of Ti-HA coatings is dependent on the Ti substrate surface: a rough metallic substrate enhanced the production and mineralization of the bone matrix compared to a smoother one, therefore enhancing the osseointegration capability [316].…”
Section: Cation-substituted Hydroxyapatitesmentioning
confidence: 99%
“…In addition, it was reported that HA coating on 316 L stainless steel improved the corrosion behavior and biocompatibility of metallic implant and bone Osseointegration simultaneously [24]. Also, Surmeneva et al prepared the HA coatings with different Ti contents on a Ti-6Al-4 V alloy, which was considered to be a possible candidate for biomedical applications [25].…”
Section: Ceramic Coatings Typesmentioning
confidence: 99%
“…As shown in Fig. 11, the GO + Nd coating has a homogeneous surface because the barrier layer does not allow corrosive ions into the coating surface, 76,77 indicating the strong physisorption on the alloy surface of the GO + Nd-based coating. The alloy dissolution has been controlled by the impermeable GO + Nd sheet on the alloy surface as shown in the electrochemical characterization.…”
Section: Electrochemical Study Of Corrosion Inhibitionmentioning
confidence: 99%